2016
DOI: 10.1177/1012690216633444
|View full text |Cite
|
Sign up to set email alerts
|

Risky bodies, risky spaces, maternal ‘instincts’: Swimming and motherhood

Abstract: Swimming and aquatic activity are fields in which gendered, embodied identities are brought to the fore, and the co-presence of other bodies can have a significant impact upon lived experiences. To date, however, there has been little research on sport and physical cultures that investigates how meanings associated with space impact upon women's embodied experiences of participating in swimming, specifically in the presence of their young children. Using semi-structured interviews and non-participant observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Indeed, participants considered that having a sauna and swimming was not only beneficial for their aching muscles and joints, but also positively affected their mental health. Similarly to that outlined elsewhere (Evans, 2017;Evans and Allen-Collinson, 2016;Evans and Sleap, 2012;Evans et al, 2017), participants described how swimming was relaxing, a way to clear their heads or to focus only upon the self and to be 'in the moment'. For example, Haya described how 'you forget everything in the world, when you're in the water'.…”
Section: Swimming and The Care Of The Selfmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, participants considered that having a sauna and swimming was not only beneficial for their aching muscles and joints, but also positively affected their mental health. Similarly to that outlined elsewhere (Evans, 2017;Evans and Allen-Collinson, 2016;Evans and Sleap, 2012;Evans et al, 2017), participants described how swimming was relaxing, a way to clear their heads or to focus only upon the self and to be 'in the moment'. For example, Haya described how 'you forget everything in the world, when you're in the water'.…”
Section: Swimming and The Care Of The Selfmentioning
confidence: 99%
“…For example, research outlined how mothers with pre-school aged children engaging in swimming were subjected to the judgemental gaze of other participants (often attributed to male ‘others’, but also inclusive of other mothers), through which they perceived others to not only evaluate their own body shape and conduct, but also their parenting techniques and their children's behaviour. Although mothers reported that they felt more comfortable in their bodies due to their children taking the attention of potential observers, this did not lead to a disengagement from dominant gendered discourses; rather, it shifted disciplinary techniques from self to children (Evans, 2017; Evans and Allen-Collinson, 2016; Evans et al, 2017).…”
Section: Lived Experiences Of Swimming Spaces and Foucauldian Power I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, and germane to the experience of temperature in the aquatic environment, Evans et al (2017) analyse how mothers monitor their young children's corporeal displays of temperature, being keenly aware of their children's 'goose pimples' as a reaction to the cold. Understanding experientially that such corporeal indicators signal a state of being cold, their appearance often results in the cessation of aquatic activity and retreat towards warmer areas.…”
Section: The Sensory Turn and The Lived Sense Of Temperaturementioning
confidence: 99%
“…Discussions within the team 'brought back' many of these memories for him, whilst his insider knowledge of the language and meanings associated with competitive swimming allowed him to act as a critical sounding board for G. Moreover, as a critical sociologist who had previously conducted research upon several non-competitive groups' subjective experiences of swimming (Evans and Allen-Collinson, 2016;Evans et al, 2017), he had been considering ways to study such experiences for a number of years and could draw on experience of the ways in which other groups described their experiences.…”
Section: Approaches To Bracketing In a Familiar Settingmentioning
confidence: 99%